2008
DOI: 10.1007/s10792-008-9258-7
|View full text |Cite
|
Sign up to set email alerts
|

Allergic reaction to hyaluronidase after retrobulbar anaesthesia: a case series and review

Abstract: Although rare and mostly benign, allergy to HA should be included in the differential diagnosis when chemosis, proptosis and restriction of eye movements occur after parabulbar or retrobulbar anaesthesia. The authors feel that the beneficial effect of HA in small volumes of RA warrants its use despite this potential complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…Delaere et al 34 reported cases of probable allergy that responded quickly to corticosteroid treatment. Eberhart et al 35 reported three cases of angioedema following the use of hyaluronidase.…”
Section: Adverse Effects On the Eyementioning
confidence: 99%
“…Delaere et al 34 reported cases of probable allergy that responded quickly to corticosteroid treatment. Eberhart et al 35 reported three cases of angioedema following the use of hyaluronidase.…”
Section: Adverse Effects On the Eyementioning
confidence: 99%
“…The initial manifestations were influenced by the route of administration: when given at a local site, localized angioedema or urticaria developed;6,10,11 when given intravenously, most patients presented with anaphylactic shock, urticaria, or dyspnea 3. Our patient was administered hyaluronidase via an intrathecal route at a relatively high dose of 1,500 IU.…”
Section: Discussionmentioning
confidence: 88%
“…However, the cumulative dose is not related to clinical manifestations 3. Most of the patients with hyaluronidase allergy had a positive skin prick test or intradermal test 6,10. When hyaluronidase is supposed to be administrated at high-dose hyaluronidase via intravenous or intrathecal routes, skin prick test could be a useful way to predict systemic allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…5 Additionally, when patients are found to be allergic exclusively to hyaluronidase, the reaction is often localized. The clinical picture is often cloudy: patients do not know to which type of bee they are allergic or to what component of the venom.…”
Section: Discussionmentioning
confidence: 99%
“…3 The honeybee, Apis mellifera (Api-m), has 10 known allergenic substances ( Table 2). 5 A review of the dermatologic literature did not reveal any cases of anaphylaxis or allergy to hyaluronidase. 4 The YJ, Vespula vulgaris (Ves-v), has 5 known allergenic substances.…”
Section: Venom Classificationmentioning
confidence: 97%